Effectiveness of 808 nm Near Infrared (NIR) Laser Photobiomodulation for Accelerating Postoperative Wound Healing: Effectiveness of 808 nm near infrared (NIR) laser - Nurfitri, Waode Erimelga; Astuti, Suryani Dyah; Widiyanti, Prihartini; Wibowo, Ricky; Wibowo, Hery; Arifianto, Deny; Winarno; Yaqubi, Ahmad Khalil; Nurdin, Muhammad; Abd Razak, Nasrul Anuar (Journal of Lasers in Medical Sciences, 2025)
Introduction: Inadequate wound treatment can lead to complications like methicillinresistant Staphylococcus aureus (MRSA) infections, increased medical risks, and skin ulcers. Antimicrobial resistance is a global health threat, and Indonesia’s injury prevalence has increased. Laser photobiomodulation therapy, using near-infrared (NIR) wavelengths, has shown potential in accelerating wound healing by stimulating cellular energy, enhancing blood flow, reducing inflammation, and promoting cell proliferation and collagen synthesis. Methods: Each treatment sample received NIR therapy for 15 minutes per session on days 0, 1, 2, 3, and 5. Wound measurements were recorded, and blood samples were collected for laboratory testing to assess the effectiveness of laser therapy in postoperative wound healing. Meanwhile, the control group did not receive therapy but underwent wound measurements and blood sample collection. The data obtained were analyzed using the SPSS non-parametric Friedman test to compare the mean values of TNF-α, IL-1β, and TGF-β1 expression between the control and therapy groups. The MannWhitney test followed this to determine whether there were significant differences between the groups. A significance level of P<0.05 was used. Results: The use of NIR laser therapy in the treatment group resulted in a 35% reduction in wound length and a 46% reduction in wound width. In the control group, wound length decreased by 30%, while wound width decreased by 26%. These results indicate that NIR therapy is effective in tissue regeneration, as evidenced by the reduction in wound size due to granulation formation and re-epithelialization. Statistical analysis of laboratory assessments showed significant differences in IL-1β and TGF-β1 cytokine expression (P<0.05) in the treatment group, while TNF-α expression did not show a significant difference (P>0.05) between the two groups. Conclusion: Clinical assessment shows that NIR has an effect on the formation of better wound tissue and shows good wound quality.